Analisis Kebutuhan Daya Pompa Pada Kapal Cargo - Sugeng Marsudi; Alya Ramadani (Departemen Teknik Kelautan Universitas Hasanuddin, 2021)
The need for electrical power is between the initial design of the ship and the conditions in the field. In the end, it can be proven theoretically that the planning of the electrical system on the ship can be implemented in real terms and in accordance with the applicable regulations so that during the installation of electrical installations on the ship and for future purposes it can be relied on and satisfied for the shipowner. is to analyze and process data, it will get an analysis of the power requirements of the cargo ship pump. From the results of the calculation of the pump power used, it can be seen that the largest pump power needed when the ship is in an emergency at night is 46.76 Kw, then this amount of power becomes the standard in the selection of auxiliary engines so that the power requirements in these conditions can be met.